What Explains Stock Markets’ Vulnerability to the 2007–2008 Crisis? - Didier, Tatiana; Love, Inessa; Peria, Maria Soledad Martinez (2012)
This paper examines the determinants of stock markets' vulnerability to the 2007-2008 crisis. Given that the United States (US) was the crisis epicenter, the authors analyze the factors driving the co-movement between US returns and stock returns in 83 countries. The analysis distinguishes between the period before and after the collapse of Lehman Brothers. The findings indicate that the main channel of transmission was financial. There is also evidence of a "wake-up call" or "demonstration effect" in the first stage of the crisis, because countries with vulnerable banking and corporate sectors exhibited higher co-movement with the US market. However, despite a collapse in trade across countries, the analysis does not find support for this channel of transmission.